Rituximab in routine care of severe active rheumatoid arthritis - Krause, Andreas; Aries, P. M.; Berger, S.; Fiehn, C.; Kellner, H.; Lorenz, Hanns-Martin; Meier, L.; Müller, G. A.; Müller-Ladner, U.; Schwarting, A.; Tony, H.-P.; Peters, M. A.; et al. (Zeitschrift für Rheumatologie, 2019)
ObjectiveTo assess safety, effectiveness and onset of effect of rituximab (RTX) in routine clinical treatment of severe, active rheumatoid arthritis (RA).MethodsProspective, multi-centre, non-interventional study in rheumatological outpatient clinics or private practices in Germany. RTX-naïve adult patients were to receive RTX according to marketing authorisation and at their physician’s discretion. Also according to their physician’s discretion, patients could receive a second cycle of RTX (re-treatment = treatment continuation). Major outcome was the change in Disease Activity Score based on 28-joints count and erythrocyte sedimentation rate (DAS28-ESR) over 24 weeks and during 6 months of re-treatment.ResultsOverall, 1653 patients received at least one cycle RTX; 99.2% of these had received disease-modifying antirheumatic drugs (DMARD) pre-treatment and 75.5% anti-tumor necrosis factor(TNF)‑α pre-treatment. After a mean interval of 8.0 months, 820 patients received RTX re-treatment. Mean DAS28-ESR decreased from 5.3 at baseline to 3.8 after 24 weeks (−1.5 [95% confidence interval, CI: −1.6; −1.4]), and from 4.1 at start of cycle 2 to 3.5 at study end (change from baseline: −1.8 [95% CI: −2.0; −1.7]). Improvements in DAS28-ESR and Health Assessment Questionnaire (HAQ) score occurred mainly during the first 12 weeks of RTX treatment, with further DAS28-ESR improvement until week 24 or month 6 of re-treatment. Improvements in DAS28-ESR and EULAR responses were more pronounced in seropositive patients. RF was a predictor of DAS28-ESR change to study end. Safety analysis showed the established profile of RTX.ConclusionRTX was safe and effective in a real-life setting with rapid and sustained improvement in RA signs and symptoms.